The performance of epoxy coated reinforcement: experience of the Ontario ministry of transportation. (8th September 2005) - Pianca, F.; Schell, H.; Cautillo, G.
The Ontario Ministry of Transportation has a mandate to specify cost-effective methods and materials for the construction and maintenance of provincial highway structures. In support of this mandate, the Bridge Durability Work Group initiated a performance evaluation of epoxy-coated reinforcement (ECR) in the Ontario bridge environment. Findings of the investigation, which are summarised in this paper, strongly indicate that the long-term performance of the ECR is not likely to provide the corrosion resistance or associated maintenance free service life that was originally forecast. Several Ministry structures constructed with ECR have already been rehabilitated, before achieving even a 20-year service life. Today, the Ministry must develop and adopt strategies at the time of design for service life that far exceed the expectations of only a few years ago; typically, in accordance with the new Canadian Highway Bridge Design Code, the design life of new structures is anticipated to be 75 years. A significant body of research to date indicates that ECR can at best provide marginally longer service life than black reinforcement.